2017
DOI: 10.1523/jneurosci.3771-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down Beta Enhances Bottom-Up Gamma

Abstract: Several recent studies have demonstrated that the bottom-up signaling of a visual stimulus is subserved by interareal gamma-band synchronization, whereas top-down influences are mediated by alpha-beta band synchronization. These processes may implement top-down control of stimulus processing if top-down and bottom-up mediating rhythms are coupled via cross-frequency interaction. To test this possibility, we investigated Granger-causal influences among awake macaque primary visual area V1, higher visual area V4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
110
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(133 citation statements)
references
References 78 publications
(116 reference statements)
12
110
1
Order By: Relevance
“…Recent studies using Granger causality measures have shown similar frequency‐specific interactions in selective attention, in which slow‐wave activity (e.g., α and β) in higher order visual areas modulates lower order regions, while the reverse occurs for γ oscillations (Bastos et al, ; Bonnefond, Kastner, & Jensen, ; Van Kerkoerle et al, ; Michalareas et al, ; von Stein, Chiang, & König, ). Furthermore, feedback activity in the α–β range has been found to promote the feedforward propagation of visual γ‐band activity during attentional selection (Richter, Thompson, Bosman, & Fries, ), an evidence that corroborates the regulatory role of top–down α influences observed in our study. The critical interplay between top–down α and bottom–up γ in visual processing has been also investigated using microstimulation: the electrical stimulation of V1 causes increases of gamma activity at later stages of the visual hierarchy (V4), whereas the stimulation of V4 increases alpha power in V1 (Van Kerkoerle et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies using Granger causality measures have shown similar frequency‐specific interactions in selective attention, in which slow‐wave activity (e.g., α and β) in higher order visual areas modulates lower order regions, while the reverse occurs for γ oscillations (Bastos et al, ; Bonnefond, Kastner, & Jensen, ; Van Kerkoerle et al, ; Michalareas et al, ; von Stein, Chiang, & König, ). Furthermore, feedback activity in the α–β range has been found to promote the feedforward propagation of visual γ‐band activity during attentional selection (Richter, Thompson, Bosman, & Fries, ), an evidence that corroborates the regulatory role of top–down α influences observed in our study. The critical interplay between top–down α and bottom–up γ in visual processing has been also investigated using microstimulation: the electrical stimulation of V1 causes increases of gamma activity at later stages of the visual hierarchy (V4), whereas the stimulation of V4 increases alpha power in V1 (Van Kerkoerle et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…At the cellular level, beta oscillations have been generated in both cortical and subcortical neurons, such as the intrinsic bursting neurons in cortical layer 5 (Roopun et al., ) and medium spiny neurons in the striatum (McCarthy et al., ), respectively, and may involve the interaction of various currents, such as the one between inhibitory GABA A currents and slow potassium currents (McCarthy et al., ). Circuitry mechanisms for beta generation have also been proposed in parallel and likely involve the recruitment of various supra‐ and infragranular cortical inhibitory and excitatory neural subtypes (Kramer et al., ; Lee, Whittington, & Kopppel, ; Richter, Thompson, Bosman, & Fries, ; Roopun et al., ). Through a combination of human magnetoencephalographic recordings, mice and monkey local field potentials, recently, Sherman et al.…”
Section: Discussionmentioning
confidence: 99%
“…A number of other studies have provided evidence consistent with the idea that gamma‐ and beta‐band activity constitute prediction error and expectation signals, respectively. For instance, analyses of Granger causality by Richter et al 179 . indicated that top‐down beta‐band activity targeting macaque V1 enhanced subsequent, spatially specific, stimulus‐driven ascending gamma‐band signals from V1 to V4 in a manner consistent with precision‐weighting mechanisms invoked by PP.…”
Section: Hypothesis 3: Each Level Of the Cortical Hierarchy Houses Twmentioning
confidence: 96%